An examination of the relationships between university students’ purchase intentions, behaviors, attitudes toward advertising, and the creativity of social media advertisements in sports products - KAYA, Erdi; BUYRUKOĞLU, Erhan; VAROL, İsmail and DARENDELİOĞLU, Rıza and ÇABUKCA, Nida Nur (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to examine the relationships between university students’ purchase intentions for sports products, consumer behaviors, attitudes toward advertising, and perceptions of advertising creativity, as well as the differences across demographic variables. The study was conducted with 302 students from various departments. Data were collected using four validated scales: the Purchase Intention Scale, Consumer Behavior Scale, Attitude Toward Advertising Scale, and Advertising Creativity Scale. Reliability coefficients ranged from 0.85 to 0.93, and normality tests confirmed that the data were normally distributed. Findings revealed a significant gender difference in consumer behavior (p < 0.05), with female students scoring higher than males. No significant differences were found in purchase intention, attitudes toward advertising, or perceptions of advertising creativity. Analyses by income, educational status, department, type of sport, and participation duration showed no significant effects, although longer participation in sports indicated a positive trend. In conclusion, gender was the only variable that created meaningful differences in consumer behavior. These results provide practical implications for sports marketing, particularly in leveraging advertising creativity and consumer attitudes to design more effective social media campaigns targeting university students.